2018
DOI: 10.1002/jcb.27346
|View full text |Cite
|
Sign up to set email alerts
|

The expression levels of long noncoding RNAs lnc0640 and lnc5150 and its gene single‐nucleotide polymorphisms in rheumatoid arthritis patients

Abstract: The expressions of lnc0640 and lnc5150 were alternated in the RA patients, suggesting that these lncRNAs may involve in the development of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
(98 reference statements)
0
8
0
Order By: Relevance
“…LncRNAs are reported to be involved in a variety of autoimmunity- and inflammation- related processes, and regulate gene expression in multiple mechanisms including alternative splicing, epigenetics, small RNA sponging (10, 11). Increasing studies have been performed to explore the potential role of lncRNAs on the pathogenesis of autoimmune diseases, such as RA and systemic lupus erythematosus (SLE) (1214). Our recent study demonstrated that the lnc0640, lnc5150 expression levels were alternated among RA patients, and lnc0640 rs13039216 TT genotype was statistically associated with RA susceptibility (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs are reported to be involved in a variety of autoimmunity- and inflammation- related processes, and regulate gene expression in multiple mechanisms including alternative splicing, epigenetics, small RNA sponging (10, 11). Increasing studies have been performed to explore the potential role of lncRNAs on the pathogenesis of autoimmune diseases, such as RA and systemic lupus erythematosus (SLE) (1214). Our recent study demonstrated that the lnc0640, lnc5150 expression levels were alternated among RA patients, and lnc0640 rs13039216 TT genotype was statistically associated with RA susceptibility (14).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies have been performed to explore the potential role of lncRNAs on the pathogenesis of autoimmune diseases, such as RA and systemic lupus erythematosus (SLE) (1214). Our recent study demonstrated that the lnc0640, lnc5150 expression levels were alternated among RA patients, and lnc0640 rs13039216 TT genotype was statistically associated with RA susceptibility (14). Another previous study suggested that aberrant lncRNA expression level in peripheral blood mononuclear cells (PBMCs) could be a potential biomarker for RA diagnosing (13).…”
Section: Introductionmentioning
confidence: 99%
“…Single nucleotide polymorphism (SNP) plays key role in disordered lncRNA (Castellanos-Rubio and Ghosh, 2019). For example, Zhang et al (2018) found that the level of lnc0640 in the PBMCs of RA patients was significantly increased compared with control, while the level of lnc5150 was significantly reduced. The disordered lnc0640 and lnc5150 were correlated with CRP, and the lnc5150 was correlated with the ESR.…”
Section: Lncrnas In Pbmcsmentioning
confidence: 99%
“…previously identified two novel lncRNAs, lnc0640 and lnc5150, which played a role in the development of SLE and the effect of lnc0640 and lnc5150 in RA was hereby explored. [24] The expression of lnc0640 in PBMCs of RA patients was significantly increased, whereas the expression of lnc5150 was significantly decreased. And the two lncRNAs were found to be significantly associated with the level of serum CRP.…”
Section: Dysregulated Expression Of Lncrnas In Ramentioning
confidence: 99%